Preparation of halide sensors by means of co-precipitation of silver sulphide and silver halide - Rajbhandari, Armila; Manandhar, Krishna; Pradhananga, Raja Ram (Journal of Nepal Chemical Society, 2013)
Halide sensors have been prepared in the laboratory by means of co-precipitation of silver sulphide and silver halide and is used for the determination of iodide, bromide and chlorides ions. The iodide sensors show a Nernstian response in the concentration range of 10-1 to 10-6M iodide ions, bromide sensors show a linear response in the concentration range of 10-1 to 10-5M bromide ions while chloride sensors show linear response upto the concentration range of 10-4M chloride ions. The response time of all the electrodes, is < 1minute. The iodide sensors were found to be selective towards iodide ions in the presence of Cl- and Br- ions while bromide and chloride sensors interferred by iodide ions as indicated by selectivity coefficient values of 3.98 and 48.9 respectively. These sensors have been successfully applied for potentiometric titrations. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9390 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 168-173 Uploaded date: 12/20/2013